First record of the mustelid Trochictis (Carnivora, Mammalia) from the early Late Miocene (MN 9/10) of Germany and a re-appraisal of the genus Trochictis. (3rd August 2021) - Morlo, Michael; Le Maitre, Anne; Bastl, Katharina; Engel, Thomas; Lutz, Herbert; Lischewsky, Bastian; Berg, Axel von; Nagel, Doris
ABSTRACT: We present the first record of the mustelid Trochictis from the Late Miocene (MN 9/10) of Germany, a partial mandible with p4, m1, and m2 from Eppelsheim. Trochictis peignei sp. nov. is characterised by the combination p4 with a distal accessory cuspid and a basal lingual enlargement, m1 with a length/width index larger than 2.5, a rounded lingual wall of the paraconid, an entoconulid present, the metaconid as high as the paraconid, and cuspules present on the posterior talonid edge, and m2 with a very reduced talonid. Comparison to similar sized Middle and Late Miocene mustelids and a stratocladistic analysis place T. peignei sp. nov. closest to T. narcisoi from MN 9 of Can Llobateras, T. depereti from several MN 6 to MN 7/8 European localities, and cf. Trochictis sp. from MN 9 of Rudabánya. We also suggest synonymy of T. carbonaria and T. artenensis and verify that m2 of Trochictis occasionally is double-rooted. The analysis does not corroborate a close relationship of Trochictis to Taxodon or the subfamily Ictonychinae, but can also not discard confidently such an assignment. With a body mass of about 3 kg, Trochictis peignei sp. nov. represents the hitherto smallest described carnivoran of the Eppelsheim Formation.